2014
DOI: 10.4172/2155-9600.1000334
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cellulose and Nanocellulose From Pomelo (Citrus grandis) Albedo

Abstract: Pomelo (Citrus grandis) peel is one of the under-utilized waste materials that have potential in the production of functional ingredients, due to its high fiber content. This study was conducted to isolate and characterize cellulose and nanocellulose from pomelo albedo. Cellulose was prepared via alkali treatment followed by bleaching process, while nanocellulose was produced via hydrolysis using sulfuric acid. The physicochemical and structural properties of the produced materials were characterized using pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Crystallinity index for both celluloses is found to be 100%. Similar studies were observed from cellulose of pomelo albedo peel by Zain et al (2014). The enlarged crystallinity of each celluloses were additionally expected to justify their stiffness, rigidity and strength (Alemdar & Sain 2008;Azubuike & Okhamafe 2012).…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 72%
See 3 more Smart Citations
“…Crystallinity index for both celluloses is found to be 100%. Similar studies were observed from cellulose of pomelo albedo peel by Zain et al (2014). The enlarged crystallinity of each celluloses were additionally expected to justify their stiffness, rigidity and strength (Alemdar & Sain 2008;Azubuike & Okhamafe 2012).…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 72%
“…This amounts to 77.77% yield, considering that the cellulose content of the peel was determined to be 27g / 100 g of dry matter. The cellulose content and yield from jackfruit peel is found to be higher than other peels including albedo peel (21.29±1.90 %, Zain et al, 2014), orange (24. 06% Bicu & Mustata, 2013) and rambutan (24.28%, Oliveira et al, 2016).…”
Section: Yield Of Cellulose (%)mentioning
confidence: 81%
See 2 more Smart Citations
“…Crystallinity index is the ratio of the diffraction from a crystalline region to the total diffraction of sample Nor et al (2014). The value of crystallinity index (CI) was calculated using empirical Segal equation (Pereira, Herman, Maria, Daniella, Sandra and Maria 2011; Saxena 2013; Lani et al 2014).…”
Section: Crystallinity Analysismentioning
confidence: 99%